Analisis Tingkat Kesehatan Bank Aceh Syariah pada Tahun 2018-2022 Menggunakan Metode RGEC (Risk Profile, Good Corporate Governance, Earning dan Capital) - Ahmad Fauzul Hakim Hasibuan; Ainun Marziah; Nurul Husna; Nurilda Safira (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This Research Aims To Analyze The Soundness Of Bank Aceh Syariah During The 2018-2022 Period Using Qualitative Methods And Quantitative Descriptive Approaches And RGEC Methods (Risk Profile, Good Corporate Governance, Earnings, And Capital). This Research Method Uses Qualitative And Quantitative Research Types. The data used in this research is secondary data, namely the 2018-2022 financial statements. This data was obtained by direct download from the Bank Aceh Syariah website. The analysis was carried out with reference to BI Regulation No.13/1/PBI/2011 and BI Circular Letter No.13/24/DPNP/2011 concerning the Assessment of the Soundness Level of Commercial Banks. As well as OJK Regulation No.8/POJK.03/2014 and OJK Circular Letter No.10/SEOJK.03/2014 Concerning Assessment of Soundness Level of Sharia Commercial Banks and Sharia Business Units. The research results show that overall, Bank Aceh Syariah in the 2018-2022 period is in good health. This can be seen from the evaluation of the Risk Profile (NPF, FDR), Good Corporate Governance (GCG), Earnings (ROA, BOPO), and Capital (CAR). In 2018 this bank earned a composite rating of 3 (fairly healthy), while in 2019-2022 this bank earned a composite rating of 2 (healthy). Keywords: Bank Health, Risk Profile, Good Corporate Governance, Earnings, Capital.